"2030 City Tour". New paradigm for intervention in the XXI century cities - Martínez de Haro, Alvaro Planchuelo (Journal of Planner and Development, 2020)
THE ACTUAL SOCIETY MODELOur society model has been showing signs of exhaustion since the end of the XX century. The recent appearance of the Covid-19 virus is another consequence of humanity's distance from Nature and the environment it inhabits. Also, climate change, environmental deterioration, loss of biodiversity, overexploitation of natural resources, and social inequality are some of the consequences derived from this separation between society and Nature. We must change our operating habits. Inevitably from a society based on the market, hyper consumption, fossil energy and individual enrichment at all costs, we will have to change to another with a more sustainable model.